2017
DOI: 10.1002/ajmg.a.38337
|View full text |Cite
|
Sign up to set email alerts
|

Craniosynostosis in patients with RASopathies: Accumulating clinical evidence for expanding the phenotype

Abstract: RASopathies are phenotypically overlapping genetic disorders caused by dysregulation of the RAS/mitogen-activated protein kinase (MAPK) signaling pathway. RASopathies include Noonan syndrome, cardio-facio-cutaneous (CFC) syndrome, Costello syndrome, Neurofibromatosis type 1, Legius syndrome, Noonan syndrome with multiple lentigines, Noonan-like syndrome, hereditary gingival fibromatosis, and capillary malformation/arteriovenous malformation syndrome. Recently, six patients with craniosynostosis and Noonan synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 19 publications
(27 reference statements)
2
35
0
Order By: Relevance
“…Craniosynostosis has been recently implicated as a comorbidity of NS [23], and 5 patients (3 with PTPN11, 1 with KRAS, and 1 with SOS1 mutations) were diagnosed as having craniosynostosis (Tables 1 and 3). Twelve of 35 patients (34.3%) exhibited otolaryngeal diseases including hearing disorders, otitis media, enlarged tonsil, and adenotrophy (Tables 1 and 3).…”
Section: Clinical Characteristics Of Genetically Diagnosed Ns Patientsmentioning
confidence: 99%
“…Craniosynostosis has been recently implicated as a comorbidity of NS [23], and 5 patients (3 with PTPN11, 1 with KRAS, and 1 with SOS1 mutations) were diagnosed as having craniosynostosis (Tables 1 and 3). Twelve of 35 patients (34.3%) exhibited otolaryngeal diseases including hearing disorders, otitis media, enlarged tonsil, and adenotrophy (Tables 1 and 3).…”
Section: Clinical Characteristics Of Genetically Diagnosed Ns Patientsmentioning
confidence: 99%
“…Among RASopathies, craniosynostosis appears to be consistently associated with NS and CFC syndrome only, and with mutations limited to PTPN11, SHOC2, KRAS , and BRAF (Takenouchi et al, 2014 ; Addissie et al, 2015 ; Ueda et al, 2017 ). In the Ueda et al report ( 2017 ), 3 out of 34 NS patients (9%) and 6 out of 18 CFC patients (33%) had craniosynostosis, and craniosynostosis affected all patients with mutations in KRAS . This strong genotype-phenotype association suggests specific mechanisms of pathology, worthy of investigation.…”
Section: Gene-related Syndromic Craniosynostosismentioning
confidence: 99%
“…It had been shown by Shukla that some components of the RAS/MAPK signaling pathway mediate dysregulated cranial development caused by pathogenic variants in fibroblast growth factor receptor (FGFR) genes (Shukla, Coumoul, Wang, Kim, & Deng, ). In addition, different studies have shown consistent association between craniosynostosis and NS patients with SHOC2 , KRAS , and PTPN11 pathogenic variants (Addissie et al, ; Takenouchi et al, ; Ueda, Yaoita, Niihori, Aoki, & Okamoto, ), and CFCS patients with KRAS and BRAF pathogenic variants (Ueda et al, ). Recently, the first patient with NSML ( PTPN11 pathogenic variant) and craniosynostosis was reported (McDonald et al, ).…”
Section: Introductionmentioning
confidence: 89%